2021
DOI: 10.1016/j.vgie.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic radiofrequency ablation for palliative treatment of hilar cholangiocarcinoma

Abstract: Background and Aims Recent data support a role for endoscopic radiofrequency ablation (RFA) in unresectable cholangiocarcinoma by improving stent patency and overall survival. Methods We describe 3 patients with inoperable cholangiocarcinoma with jaundice and cholestasis who were recommended palliative chemotherapy. They underwent endoscopic retrograde cholangiopancreatography with single-operator cholangioscope and intraductal RFA. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Potential bias may arise from the type of stents used in such interventions, as a recent randomized controlled multicenter trial showed that in the case of self-expandable uncovered metallic stents RFA did not prove any positive impact on either stent patency rate or survival [ 23 ]. Efficacy might also be influenced by the location of strictures, as RFA has been of greatest interest in hilar lesions where maintaining stent patency and technical success are far more challenging [ 24 , 25 ]. Therefore, further studies comparing different devices, locations, and therapy protocols are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Potential bias may arise from the type of stents used in such interventions, as a recent randomized controlled multicenter trial showed that in the case of self-expandable uncovered metallic stents RFA did not prove any positive impact on either stent patency rate or survival [ 23 ]. Efficacy might also be influenced by the location of strictures, as RFA has been of greatest interest in hilar lesions where maintaining stent patency and technical success are far more challenging [ 24 , 25 ]. Therefore, further studies comparing different devices, locations, and therapy protocols are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic RFA also appears to be an effective method for restoration of malignant biliary stent obstruction. RFA therapy alone compared to PS placement for the treatment of occluded metal stents showed a significant increase in biliary patency following RFA as well as low risk of short-term adverse events stents [96][97][98].…”
Section: Radiofrequency Ablationmentioning
confidence: 95%
“…RFA allows for tissue necrosis through thermal energy, leading to necrosis of tumor cells and good control of tumor growth. A study conducted in 2017 demonstrated increased survival in patients with advanced CC undergoing biliary drainage with stent placement associated with RFA [33].…”
Section: Palliationmentioning
confidence: 99%